Effect of Lysozyme on Ionic Forms of Spores of Clostridium perfringens Type A - Ando, Yoshiaki (1975)
H spores of Clostridium perfringens type A (two strains) were more sensitive to germination by lysozyme than native spores. Resistance to lysozyme of H spores was restored by calcium loading.